1134 Does open-plan offices suite staff in a psychiatric care setting?. (24th April 2018) - Stöllman, Å; Eriksson, T; Vingård, E
Abstract : Introduction: In 2013, all psychiatric units (in-and outpatient) in Uppsala, Sweden, were relocated together into a new building at the hospital area. 500 employees moved from mainly cell offices to open design offices without flexible seating. Occupational medicine made an evaluation to investigate how the psychosocial work environment was affected by the change. Methods: Semi structured focus groups interviews, with a total of eight group interviews, four months before the relocation and 14 months after. The groups were divided by professional groups such as nurses, physicians, psychologists and in administrative groups such as managers, management team and staff. The participants were randomly invited to the interviews, all together 55 persons participated before, and 46 persons after the relocation. The interviews were transcribed and analysed using qualitative data analysis. Results: Overall, the staff experienced difficulties performing their duties in an optimal way in the open workplaces. Both the psychosocial environment, the organisation and logistics was affected, making the workflow more inefficient. The closeness to the hospital was appreciated by all groups. The staff perceived the managers to be both near and far away. Contacts with managers seated in an open workplace became more visible, while managers seated in specific head departments were not easily accessible. The hierarchy of the organisation became more visible in the open design office. Conclusion: An important contribution from this evaluation is to learn from what works for the staff and find success factors for a good work environment in the open workplaces. For example, allocate time to educate staff in new methods and approaches needed in the open workplace, seat managers together with staff to increase flow of information and to strengthen relations, promote flexibility by modern information technology and continuously evaluate and adjust to ensure that offices are suited optimally for the organisation's needs.